Echo Cancellation For Voice Over Internet Protocol (VOIP) Networks - Ganesan , Periakaruppan (2005)
In this research, a Packet Based Echo Canceller (PBEC) is introduced as a new solution for Echo Cancellation in the VoIP network. The PBEC would receive the packets that come from the gateway and cancel the echo by using the conventional adaptive filter algorithms.